Pharmacogenomics of platelet responsiveness to aspirin. (October 2007) - Faraday, Nauder; Becker, Diane M; Becker, Lewis C
Aspirin is the most widely used drug in the world for cardiovascular protection. Aspirin''s ability to suppress platelet function varies widely among individuals and lesser suppression of platelet function is associated with increased risk of myocardial infarction, stroke and cardiovascular death. Platelet response to aspirin is a complex phenotype involving multiple genes and molecular pathways. Aspirin response phenotypes can be categorized as directly or indirectly related to cyclooxygenase-1 (COX-1) activity, with phenotypic variation indirectly related to COX-1 being much more prominent. Recent data indicate that variability in platelet response to aspirin is genetically determined, but the specific gene variants that contribute to phenotypic variation are not known. An understanding of the relationship between genotype, aspirin response phenotype and clinical outcome will help to bring about a personalized approach to antiplatelet therapy that maximizes antithrombotic benefit whilst minimizing bleeding risk for individual patients.